Brexit: Theresa May's Red Lines Get Tangled up in Her Red Tape. A Commentary on the White Paper - Polly Ruth Polak (European Papers, 2017)
(Series Information) European Papers - A Journal on Law and Integration, 2017 2(1), 403-410 | European Forum Insight of 21 May 2017 | (Table of Contents) I. Introduction. - II. The White Paper. - III. The Free Trade Agreement. - IV. The customs agreement. - V. Conclusion. | (Abstract) The 29 March 2017 is now set to become the historical day Art. 50 TEU was triggered for the first time ever. Equally, unprecedented negotiations, in which the United Kingdom and the European Union will settle their divorce, will follow. With the aim of proving that the UK Government has the necessary negotiating strategy, it recently published a White Paper on its exit from and new partnership with the EU. Despite the promises, this Paper is far from providing certainty and clarity. However, it is also a step away from a previous superficial and simplistic approach to Brexit. In this Insight, I explain why the White Paper is riddled with contradictions and why, nonetheless, this confusing and vague exposition of what the UK will be seeking to achieve from its withdrawal is a welcome though disguised acknowledgment of the complexities that Brexit will entail.